2018
DOI: 10.1159/000485648
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low Contrast Volume for Patients with Advanced Chronic Kidney Disease Undergoing Coronary Procedures

Abstract: Background/Aims: Contrast induced nephropathy (CIN) is associated with adverse clinical outcomes in patients undergoing coronary interventions, particularly in patients with advanced chronic kidney. The study was aimed to assess the real-life feasibility and safety of ultra-low volume coronary procedures in patients with advanced chronic kidney disease. Methods: A prospective study that included patients with an estimated glomerular filtration rate (eGFR) <45 mL/min/1.73 m2) was conducted. Coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…30 The efficient and judicious use of CM through "ultra-low contrast technique" has been described to be feasible, effective, and safe; this technique involved use of small catheters without side-holes and approach to minimize CM injection. 32 Another approach thought to reduce the risk of CIN is by using iso-osmolar CM (iodixanol), however, current evidence does not show the superiority of iso-osmolar CM compared to low-osmolar CM. 33 A randomized controlled trial also showed that radial access has a lower risk of AKI compared to femoral access, which might be elucidated by reduction of bleeding events, renal circulation embolization, or by a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The efficient and judicious use of CM through "ultra-low contrast technique" has been described to be feasible, effective, and safe; this technique involved use of small catheters without side-holes and approach to minimize CM injection. 32 Another approach thought to reduce the risk of CIN is by using iso-osmolar CM (iodixanol), however, current evidence does not show the superiority of iso-osmolar CM compared to low-osmolar CM. 33 A randomized controlled trial also showed that radial access has a lower risk of AKI compared to femoral access, which might be elucidated by reduction of bleeding events, renal circulation embolization, or by a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Dextran may also be used in OCT‐guided PCI which seemed to be non‐nephrotoxic if administered <100 ml 30 . The efficient and judicious use of CM through “ultra‐low contrast technique” has been described to be feasible, effective, and safe; this technique involved use of small catheters without side‐holes and approach to minimize CM injection 32 . Another approach thought to reduce the risk of CIN is by using iso‐osmolar CM (iodixanol), however, current evidence does not show the superiority of iso‐osmolar CM compared to low‐osmolar CM 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common indication was NSTEMI (25 patients) followed by stable angina pectoris (5 patients), and 16 patients underwent subsequent coronary angioplasty. CIN occurred in 3 patients increase in serum cystine level but not on creatinine levels 48 h following coronary procedure [20].…”
Section: Discussionmentioning
confidence: 87%
“…Group (A): which included [20] whose cv/gfr ratio < 2. Group (B): which included [21] patients in whom cv/gfr ratio > 2 but still < MACD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one prospective study and another retrospective analysis showed that ultra-low contrast techniques guided by only angiography (without IVUS and OCT) is feasible and can safely be used in patients with CKD [26, 27]. These single arm studies showed that contrast dose might be reduced to a median volume of 13 to 15.2 ml for diagnostic angiography and 13 to 17.1 ml for PCI, which was associated with a low rate of CIN [26, 27]. Although this approach is cheaper compared with IVUS- or OCT-guided procedures, there are some concerns about its long-term outcomes, i.e., whether ultra-low contrast PCI without intravascular imaging ensures optimal results.…”
Section: Current Clinical Evidencementioning
confidence: 99%